2012
DOI: 10.4038/vingnanam.v10i1.4075
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of soil transmitted helminthes infestation among preschool children of Vadamaradchi Educational Zone

Abstract: This cross sectional study was designed to find out the prevalence of soil transmitted helminth infestation and associated factors among preschool children of Vadamaraadchi Educational Zone in Jaffna district. One preschool was randomly selected from each division (3) of the educational zone, and all the children (n=103) of selected schools were included in the study. Faecal samples were collected and examined by direct wet smear, salt flotation and formal ether concentration techniques. Demographic, socio-eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…In the present study, 43.67% children used toilet, 22% children used pot toilet, 17.67% children used diaper/cloth and only 16.67% people used open fields as defecation place. The prevalence of intestinal parasites was found to be higher (8.33%) in the persons who used open field as defecation place which is in agreement with Karunaithas et al (2011). This study demonstrated significant association between hand washing after using toilet, and rate of intestinal parasites infestations.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, 43.67% children used toilet, 22% children used pot toilet, 17.67% children used diaper/cloth and only 16.67% people used open fields as defecation place. The prevalence of intestinal parasites was found to be higher (8.33%) in the persons who used open field as defecation place which is in agreement with Karunaithas et al (2011). This study demonstrated significant association between hand washing after using toilet, and rate of intestinal parasites infestations.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, majority of the parents had school education up to Grade 8 or above and they were aware of parasitic infections (paternal education: 44% passed Grade 8, 26% passed O/L, and 4% passed A/L; maternal education: 42% passed Grade 8, 30% passed O/L, and 3% passed A/L). Similar findings were observed in failure of the parents to respond to a study carried out in Sri Lanka in 2011 [ 10 ].…”
Section: Discussionsupporting
confidence: 85%
“…However, in comparison with recent studies, the prevalence of STH reported in this study was higher than in the urban and rural areas, while it was lower than that in other plantation sectors in Sri Lanka. 22,2324,34,35,36 One to 6 year children showed a slightly higher prevalence (29.7%) than 7 to 12 year old children (24.7%). This difference may be due to various reasons including a lack of awareness, increased soil related activities of younger children than adults, and the prevailing poor health and personal hygiene in the plantation sector.…”
Section: Discussionmentioning
confidence: 95%